Association Between Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio with Global Registry of Acute Coronary Events Risk Score in Acute Myocardial Infarction - Alvenus Willim, Herick; Prayogi Pakpahan, Simon; Suprihatin, Elnath; Agustyana, Andini; Gusti Arilaksono, Dwisetyo; -, Suhardi (Cermin Dunia Kedokteran, 2021)
Background. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are novel inflammatory markers in cardiovascular diseases. Global Registry of Acute Coronary Events (GRACE) risk score is a scoring system to predict risk of mortality in acute coronary syndrome. Objective. To investigate the association between NLR and PLR with GRACE risk score in acute myocardial infarction (AMI) patients. Method. A cross-sectional study using data from medical records of AMI patients. Spectrum of AMI includes ST-segment elevation myocardial infarction (STEMI) or non-STEMI. Data analysis was performed using SPSS 20. Results. A total of 136 patients were included, 72.1% male with mean age 56.1 ± 10.5 years. NLR (p<0.001) and PLR (p<0.001) among GRACE risk score groups were significantly different. Mean NLR in low, intermediate, and high GRACE risk score groups were 3.5 ± 2.4, 6.0 ± 4.8, and 7.9 ± 3.9, respectively. Mean PLR in low, intermediate, and high GRACE risk score groups were 117.2 ± 62.3, 183.7 ± 95.8, and 209.9 ± 83.4, respectively. NLR (r=0.527; p<0.001) and also PLR (r=0.496; p<0.001) was significantly positively correlated with GRACE risk score. Conclusion. NLR and PLR are simple and cost effective inflammatory markers to predict GRACE risk score and an additional prognostic tool in AMI.Pendahuluan. Rasio neutrofil-limfosit (RNL) dan rasio platelet-limfosit (RPL) merupakan petanda inflamasi penyakit kardiovaskular baru. Skor risiko Global Registry of Acute Coronary Events (GRACE) digunakan untuk prediksi risiko mortalitas sindrom koroner akut. Tujuan. Menyelidiki hubungan antara RNL dan RPL dengan skor risiko GRACE pada pasien infark miokard akut (IMA). Metode. Studi potong lintang atas data rekam medis pasien IMA. Spektrum IMA meliputi IMA dengan Elevasi Segmen ST (IMA-EST) dan IMA Non-elevasi Segmen ST (IMA-NEST). Analisis data menggunakan SPSS 20. Hasil. Sebanyak 136 pasien diteliti, 72.1% laki-laki dengan usia rerata 56.1 ± 10.5 tahun. Terdapat perbedaan signifikan nilai RNL (p<0.001) dan RPL (p<0.001) di antara kelompok skor risiko GRACE. Rerata RNL kelompok skor risiko GRACE rendah, sedang, dan tinggi adalah masing-masing 3.5 ± 2.4, 6.0 ± 4.8, dan 7.9 ± 3.9. Rerata RPL kelompok skor risiko GRACE rendah, sedang, dan tinggi adalah masing-masing 117.2 ± 62.3, 183.7 ± 95.8, dan 209.9 ± 83.4. RNL memiliki korelasi positif signifikan dengan skor risiko GRACE (r=0.527; p<0.001). RPL juga memiliki korelasi positif signifikan dengan skor risiko GRACE (r=0.496; p<0.001). Simpulan. RNL dan RPL merupakan petanda inflamasi sederhana dan hemat biaya yang dapat memprediksi skor risiko GRACE dan memberikan nilai prognostik tambahan pada IMA.